THE INFLUENCE OF CAR, NPF, FDR ON ROA OF BPRS HIK PARAHYANGAN FOR THE YEARS 2015-2023 - Oktafia, Renny; Wulandari, Annisa Dwi; Kusuma, Shania Pradyptha; Latifah, Mutiata (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The ongoing growth of Indonesia’s Sharia banking sector underscores the necessity of assessing the financial performance of Sharia People’s Financing Banks as microfinance entities. This study examined the consequence of Capital Adequacy Ratio, Non-Performing Financing, and Financing to Deposit Ratio on Return on Assets at BPRS HIK Parahyangan. The study seeks to explore the consequence of those parameters on financial success, as shown by ROA, and to provide novel insights pertinent to financial management at this BPRS. The methodology is using quantitative analysis via multiple linear regression, tapping into secondary data sourced from the yearly financial statements of BPRS HIK Parahyangan for the years 2015 to 2023, analyzed with using SPSS 27 software. The research findings prove that CAR negatively affects ROA, whereas NPF and FDR exhibit no significant partial influence. None of them exert a concurrent influence on ROA. These findings contradict previous research that indicate a significant implication of these three parameters on the profitability of Sharia banks. The originality of the research resides in the particular research subject and the findings that offer a fresh viewpoint on the dynamics of financial ratios and its profitability